### (0) Obligation:

Runtime Complexity TRS:
The TRS R consists of the following rules:

plus(0, y) → y
plus(s(x), y) → s(plus(x, y))
lt(0, s(y)) → true
lt(x, 0) → false
lt(s(x), s(y)) → lt(x, y)
fib(x) → fibiter(x, 0, 0, s(0))
fibiter(b, c, x, y) → if(lt(c, b), b, c, x, y)
if(false, b, c, x, y) → x
if(true, b, c, x, y) → fibiter(b, s(c), y, plus(x, y))

Rewrite Strategy: FULL

### (1) DecreasingLoopProof (EQUIVALENT transformation)

The following loop(s) give(s) rise to the lower bound Ω(n1):
The rewrite sequence
plus(s(x), y) →+ s(plus(x, y))
gives rise to a decreasing loop by considering the right hand sides subterm at position [0].
The pumping substitution is [x / s(x)].
The result substitution is [ ].

### (3) RenamingProof (EQUIVALENT transformation)

Renamed function symbols to avoid clashes with predefined symbol.

### (4) Obligation:

Runtime Complexity Relative TRS:
The TRS R consists of the following rules:

plus(0', y) → y
plus(s(x), y) → s(plus(x, y))
lt(0', s(y)) → true
lt(x, 0') → false
lt(s(x), s(y)) → lt(x, y)
fib(x) → fibiter(x, 0', 0', s(0'))
fibiter(b, c, x, y) → if(lt(c, b), b, c, x, y)
if(false, b, c, x, y) → x
if(true, b, c, x, y) → fibiter(b, s(c), y, plus(x, y))

S is empty.
Rewrite Strategy: FULL

Infered types.

### (6) Obligation:

TRS:
Rules:
plus(0', y) → y
plus(s(x), y) → s(plus(x, y))
lt(0', s(y)) → true
lt(x, 0') → false
lt(s(x), s(y)) → lt(x, y)
fib(x) → fibiter(x, 0', 0', s(0'))
fibiter(b, c, x, y) → if(lt(c, b), b, c, x, y)
if(false, b, c, x, y) → x
if(true, b, c, x, y) → fibiter(b, s(c), y, plus(x, y))

Types:
plus :: 0':s → 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
lt :: 0':s → 0':s → true:false
true :: true:false
false :: true:false
fib :: 0':s → 0':s
fibiter :: 0':s → 0':s → 0':s → 0':s → 0':s
if :: true:false → 0':s → 0':s → 0':s → 0':s → 0':s
hole_0':s1_0 :: 0':s
hole_true:false2_0 :: true:false
gen_0':s3_0 :: Nat → 0':s

### (7) OrderProof (LOWER BOUND(ID) transformation)

Heuristically decided to analyse the following defined symbols:
plus, lt, fibiter

They will be analysed ascendingly in the following order:
plus < fibiter
lt < fibiter

### (8) Obligation:

TRS:
Rules:
plus(0', y) → y
plus(s(x), y) → s(plus(x, y))
lt(0', s(y)) → true
lt(x, 0') → false
lt(s(x), s(y)) → lt(x, y)
fib(x) → fibiter(x, 0', 0', s(0'))
fibiter(b, c, x, y) → if(lt(c, b), b, c, x, y)
if(false, b, c, x, y) → x
if(true, b, c, x, y) → fibiter(b, s(c), y, plus(x, y))

Types:
plus :: 0':s → 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
lt :: 0':s → 0':s → true:false
true :: true:false
false :: true:false
fib :: 0':s → 0':s
fibiter :: 0':s → 0':s → 0':s → 0':s → 0':s
if :: true:false → 0':s → 0':s → 0':s → 0':s → 0':s
hole_0':s1_0 :: 0':s
hole_true:false2_0 :: true:false
gen_0':s3_0 :: Nat → 0':s

Generator Equations:
gen_0':s3_0(0) ⇔ 0'
gen_0':s3_0(+(x, 1)) ⇔ s(gen_0':s3_0(x))

The following defined symbols remain to be analysed:
plus, lt, fibiter

They will be analysed ascendingly in the following order:
plus < fibiter
lt < fibiter

### (9) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
plus(gen_0':s3_0(n5_0), gen_0':s3_0(b)) → gen_0':s3_0(+(n5_0, b)), rt ∈ Ω(1 + n50)

Induction Base:
plus(gen_0':s3_0(0), gen_0':s3_0(b)) →RΩ(1)
gen_0':s3_0(b)

Induction Step:
plus(gen_0':s3_0(+(n5_0, 1)), gen_0':s3_0(b)) →RΩ(1)
s(plus(gen_0':s3_0(n5_0), gen_0':s3_0(b))) →IH
s(gen_0':s3_0(+(b, c6_0)))

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (11) Obligation:

TRS:
Rules:
plus(0', y) → y
plus(s(x), y) → s(plus(x, y))
lt(0', s(y)) → true
lt(x, 0') → false
lt(s(x), s(y)) → lt(x, y)
fib(x) → fibiter(x, 0', 0', s(0'))
fibiter(b, c, x, y) → if(lt(c, b), b, c, x, y)
if(false, b, c, x, y) → x
if(true, b, c, x, y) → fibiter(b, s(c), y, plus(x, y))

Types:
plus :: 0':s → 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
lt :: 0':s → 0':s → true:false
true :: true:false
false :: true:false
fib :: 0':s → 0':s
fibiter :: 0':s → 0':s → 0':s → 0':s → 0':s
if :: true:false → 0':s → 0':s → 0':s → 0':s → 0':s
hole_0':s1_0 :: 0':s
hole_true:false2_0 :: true:false
gen_0':s3_0 :: Nat → 0':s

Lemmas:
plus(gen_0':s3_0(n5_0), gen_0':s3_0(b)) → gen_0':s3_0(+(n5_0, b)), rt ∈ Ω(1 + n50)

Generator Equations:
gen_0':s3_0(0) ⇔ 0'
gen_0':s3_0(+(x, 1)) ⇔ s(gen_0':s3_0(x))

The following defined symbols remain to be analysed:
lt, fibiter

They will be analysed ascendingly in the following order:
lt < fibiter

### (12) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
lt(gen_0':s3_0(n494_0), gen_0':s3_0(+(1, n494_0))) → true, rt ∈ Ω(1 + n4940)

Induction Base:
lt(gen_0':s3_0(0), gen_0':s3_0(+(1, 0))) →RΩ(1)
true

Induction Step:
lt(gen_0':s3_0(+(n494_0, 1)), gen_0':s3_0(+(1, +(n494_0, 1)))) →RΩ(1)
lt(gen_0':s3_0(n494_0), gen_0':s3_0(+(1, n494_0))) →IH
true

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (14) Obligation:

TRS:
Rules:
plus(0', y) → y
plus(s(x), y) → s(plus(x, y))
lt(0', s(y)) → true
lt(x, 0') → false
lt(s(x), s(y)) → lt(x, y)
fib(x) → fibiter(x, 0', 0', s(0'))
fibiter(b, c, x, y) → if(lt(c, b), b, c, x, y)
if(false, b, c, x, y) → x
if(true, b, c, x, y) → fibiter(b, s(c), y, plus(x, y))

Types:
plus :: 0':s → 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
lt :: 0':s → 0':s → true:false
true :: true:false
false :: true:false
fib :: 0':s → 0':s
fibiter :: 0':s → 0':s → 0':s → 0':s → 0':s
if :: true:false → 0':s → 0':s → 0':s → 0':s → 0':s
hole_0':s1_0 :: 0':s
hole_true:false2_0 :: true:false
gen_0':s3_0 :: Nat → 0':s

Lemmas:
plus(gen_0':s3_0(n5_0), gen_0':s3_0(b)) → gen_0':s3_0(+(n5_0, b)), rt ∈ Ω(1 + n50)
lt(gen_0':s3_0(n494_0), gen_0':s3_0(+(1, n494_0))) → true, rt ∈ Ω(1 + n4940)

Generator Equations:
gen_0':s3_0(0) ⇔ 0'
gen_0':s3_0(+(x, 1)) ⇔ s(gen_0':s3_0(x))

The following defined symbols remain to be analysed:
fibiter

### (15) NoRewriteLemmaProof (LOWER BOUND(ID) transformation)

Could not prove a rewrite lemma for the defined symbol fibiter.

### (16) Obligation:

TRS:
Rules:
plus(0', y) → y
plus(s(x), y) → s(plus(x, y))
lt(0', s(y)) → true
lt(x, 0') → false
lt(s(x), s(y)) → lt(x, y)
fib(x) → fibiter(x, 0', 0', s(0'))
fibiter(b, c, x, y) → if(lt(c, b), b, c, x, y)
if(false, b, c, x, y) → x
if(true, b, c, x, y) → fibiter(b, s(c), y, plus(x, y))

Types:
plus :: 0':s → 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
lt :: 0':s → 0':s → true:false
true :: true:false
false :: true:false
fib :: 0':s → 0':s
fibiter :: 0':s → 0':s → 0':s → 0':s → 0':s
if :: true:false → 0':s → 0':s → 0':s → 0':s → 0':s
hole_0':s1_0 :: 0':s
hole_true:false2_0 :: true:false
gen_0':s3_0 :: Nat → 0':s

Lemmas:
plus(gen_0':s3_0(n5_0), gen_0':s3_0(b)) → gen_0':s3_0(+(n5_0, b)), rt ∈ Ω(1 + n50)
lt(gen_0':s3_0(n494_0), gen_0':s3_0(+(1, n494_0))) → true, rt ∈ Ω(1 + n4940)

Generator Equations:
gen_0':s3_0(0) ⇔ 0'
gen_0':s3_0(+(x, 1)) ⇔ s(gen_0':s3_0(x))

No more defined symbols left to analyse.

### (17) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
plus(gen_0':s3_0(n5_0), gen_0':s3_0(b)) → gen_0':s3_0(+(n5_0, b)), rt ∈ Ω(1 + n50)

### (19) Obligation:

TRS:
Rules:
plus(0', y) → y
plus(s(x), y) → s(plus(x, y))
lt(0', s(y)) → true
lt(x, 0') → false
lt(s(x), s(y)) → lt(x, y)
fib(x) → fibiter(x, 0', 0', s(0'))
fibiter(b, c, x, y) → if(lt(c, b), b, c, x, y)
if(false, b, c, x, y) → x
if(true, b, c, x, y) → fibiter(b, s(c), y, plus(x, y))

Types:
plus :: 0':s → 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
lt :: 0':s → 0':s → true:false
true :: true:false
false :: true:false
fib :: 0':s → 0':s
fibiter :: 0':s → 0':s → 0':s → 0':s → 0':s
if :: true:false → 0':s → 0':s → 0':s → 0':s → 0':s
hole_0':s1_0 :: 0':s
hole_true:false2_0 :: true:false
gen_0':s3_0 :: Nat → 0':s

Lemmas:
plus(gen_0':s3_0(n5_0), gen_0':s3_0(b)) → gen_0':s3_0(+(n5_0, b)), rt ∈ Ω(1 + n50)
lt(gen_0':s3_0(n494_0), gen_0':s3_0(+(1, n494_0))) → true, rt ∈ Ω(1 + n4940)

Generator Equations:
gen_0':s3_0(0) ⇔ 0'
gen_0':s3_0(+(x, 1)) ⇔ s(gen_0':s3_0(x))

No more defined symbols left to analyse.

### (20) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
plus(gen_0':s3_0(n5_0), gen_0':s3_0(b)) → gen_0':s3_0(+(n5_0, b)), rt ∈ Ω(1 + n50)

### (22) Obligation:

TRS:
Rules:
plus(0', y) → y
plus(s(x), y) → s(plus(x, y))
lt(0', s(y)) → true
lt(x, 0') → false
lt(s(x), s(y)) → lt(x, y)
fib(x) → fibiter(x, 0', 0', s(0'))
fibiter(b, c, x, y) → if(lt(c, b), b, c, x, y)
if(false, b, c, x, y) → x
if(true, b, c, x, y) → fibiter(b, s(c), y, plus(x, y))

Types:
plus :: 0':s → 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
lt :: 0':s → 0':s → true:false
true :: true:false
false :: true:false
fib :: 0':s → 0':s
fibiter :: 0':s → 0':s → 0':s → 0':s → 0':s
if :: true:false → 0':s → 0':s → 0':s → 0':s → 0':s
hole_0':s1_0 :: 0':s
hole_true:false2_0 :: true:false
gen_0':s3_0 :: Nat → 0':s

Lemmas:
plus(gen_0':s3_0(n5_0), gen_0':s3_0(b)) → gen_0':s3_0(+(n5_0, b)), rt ∈ Ω(1 + n50)

Generator Equations:
gen_0':s3_0(0) ⇔ 0'
gen_0':s3_0(+(x, 1)) ⇔ s(gen_0':s3_0(x))

No more defined symbols left to analyse.

### (23) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
plus(gen_0':s3_0(n5_0), gen_0':s3_0(b)) → gen_0':s3_0(+(n5_0, b)), rt ∈ Ω(1 + n50)